Asymmetric and non-linear adjustments in local fiscal policy - Gabriella Deborah Legrenzi (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyse the revenue-expenditure patterns of local governments, allowing for asymmetric and non-linear adjustments of local spending and taxation to disequilibrium errors. Our results provide evidence of a downward inflexibility of both local government spending and local taxation, pointing to a budget-maximising local government.
Keywords: H10; H71; C22; 330; Fiscal federalism; fly-paper effect; non-linear time-series; asymmetric adjustment; Kommunale Finanzpolitik; Flypaper-Effekt; Schätzung; Italien